2016
DOI: 10.1097/bpo.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Usefulness of Polymerase Chain Reaction as a Supplemental Diagnostic Tool in the Evaluation and the Treatment of Children With Septic Arthritis

Abstract: PCR provides supplemental information for diagnostic confirmation through an increased rate of detection of bacteria. The timing of results and the inability to provide antibiotic sensitivity are factors that limit its clinical usefulness currently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 27 publications
4
47
0
Order By: Relevance
“…Williams et al 11 used PCR for pathogen detection and reported K. kingae as the most frequently isolated pathogen (27 cases, 39.7% of all synovial fluid pathogens, while routine cultures identified K. kingae in only 2 synovial fluid samples). Two additional studies 14,16 used both conventional cultures and PCR methods of detection and reported K. kingae growth in 10% and 14% of cases. The rates of positivity of synovial fluid cultures in the 7 studies mentioned were in the range of 23.8e63%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Williams et al 11 used PCR for pathogen detection and reported K. kingae as the most frequently isolated pathogen (27 cases, 39.7% of all synovial fluid pathogens, while routine cultures identified K. kingae in only 2 synovial fluid samples). Two additional studies 14,16 used both conventional cultures and PCR methods of detection and reported K. kingae growth in 10% and 14% of cases. The rates of positivity of synovial fluid cultures in the 7 studies mentioned were in the range of 23.8e63%.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional studies reported that the use of PCR increases considerably the chances of bacterial identification in SA. 14,16 We consider surgery in the management of SA as complementary to antibiotics and not as an alternative to antibiotics and postulate that pus has to be drained and the joints have to be washed. In deep located joints like hip and shoulder, effective drainage is achieved by formal arthrotomy while arthroscopy represents an alternative.…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 18-70 % cases, no organisms can be identified (culture negative septic arthritis) [7,10]. The possible explanations for culture negative results are mistaken diagnosis; small bacterial load in sample; requirement of more sensitive diagnostic methods or samples obtained after initiation of antibiotics.…”
Section: Epidemiology and Causative Organismsmentioning
confidence: 97%
“…Gram stain and culture may become negative shortly after initiation of antimicrobial therapy whereas bacterial rDNA persists and may be detected by molecular methods several weeks later (17). Addition of 16S rDNA PCR to routine processing of joint specimens increases diagnostic yield over culture alone in paediatric septic arthritis (18).…”
Section: Discussionmentioning
confidence: 99%